Supplementary Materials Based on Constructivism Principles for Studentsâ Effective Learning - Cahyaningrum, Dewi; Wahyuni, Dewi; Sulistyawati, Hefy; *, Kristiandi (Proceeding of International Conference on Teacher Training and Education, 2016)
Learning materials that are locally relevant with the diversity of studentsâ condition and needs and meaningfulfor their learning are one of some factors influencing the studentsâ achievement.Â  However, it is not easy forteacher to provide the students with these adequate learning materials.Â  Teachers are sometimes just left with aset of textbooks to use without additional learning materials. Besides, there are just few teachers trained toadopt, adapt, and mediate locally available learning materials to meet the current needs of the students. As aresult a number of learners do not achieve the learning objective. This paper is in the form of descriptive studytalking about supplementary materials for reading skill based on constructivism principles for studentsâ effectivelearning.Â  It proposes a practical model for developing supplementary materials following constructivismprinciples by fostering teachers to do self-evaluation of their teaching and need analysis for accommodating thestudentsâ diversity condition. Supplementary materials are designed to provide students with engaging activitiesthrough which they develop skills, acquire concepts and be responsible for their learning.